Hurricane Impact Index for Assessing Direct and Indirect Hazards in Central America - Camacho Pochet, Manrique (2025)
Hurricanes rank among the most destructive natural hazards. They are complex phenomena that can cause both direct damage along their path and indirect impacts due to heavy rainfall and strong winds, with effects varying according to regional topography. In this paper, we propose a Hurricane Impact Index to assess both direct and indirect hazards, and we demonstrate its applicability to the Central American region. The index is constructed so that we can decompose these effects across multiple dimensions of time and space, enabling a detailed analysis of the intensity and distribution of hurricane impacts.